ANALISIS MUTU PELAYANAN RUMAH SAKIT DAN PENGARUHNYA TERHADAP KEPUASAN PASIEN RUMAH SAKIT IBU & ANAK (RSIA) ANDINI DI PEKANBARU - Putri, Kartika Gita; Nursanti, Aida; ', Sjahruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research held in Rumah Sakit Ibu & Anak (RSIA) Andini. The purpose of this study is to analyze the hospital service quality dimension which is consist of reliability, tangible, responsiveness, assurance and emphaty and the effect to patients’ satisfaction. Population are patient or their family in RSIA Andini. Sampling number determined by using Slovin that produce 95 person and selected by using purposive sampling method. Data analyzed by using descriptive and multiple linier regression analysis.Result of this study shows that all hospital service quality dimension consist of reliability, tangible, responsiveness, assurance and emphaty influence positive and significantly, either partially or simultaneously, to patients’ satisfaction. Assurance is the most strongest dimension that influence patients’ satisfaction, while emphaty becomes the most weakest one to patients’ satisfaction. It is recommended to the management in order to enhance some less optimum hospital service quality, particularly to the dimension of reliability, tangible and responsiveness.Keywords: Service Quality and Customer Satisfaction